Long-Term Exposure to Traffic Noise and Risk of Incident Cardiovascular Diseases: a Systematic Review and Dose-Response Meta-Analysis. - Fu, Xueru; Wang, Longkang; Yuan, Lijun; Hu, Huifang; Li, Tianze; Zhang, Jinli; Ke, Yamin; Wang, Mengmeng; Gao, Yajuan; Huo, Weifeng; Chen, Yaobing; Zhang, Wenkai; et al. (Journal of Urban Health, 2023)
While noise pollution from transportation has become an important public health problem, the relationships between different sources of traffic noise and cardiovascular diseases (CVDs) remain inconclusive. A comprehensive meta-analysis was therefore conducted to quantitatively assess the effects of long-term exposure to road traffic, railway, and aircraft noise on CVDs and relevant subtypes. We systematically retrieved PubMed, Embase, and Web of Science for articles published before April 4, 2022. Summary relative risks (RRs) and 95% confidence intervals (CIs) were estimated by the fixed- or random-effects models. In total, 23 articles were included in our meta-analysis. The risk of CVDs increased by 2% (RR 1.020, 95% CI 1.006–1.035) and 1.6% (RR 1.016, 95% CI 1.000–1.032) for every 10 dB increment of road traffic and aircraft noise. For CVD subtypes, the risk increased by 3.4% (1.034, 1.026–1.043) for stroke and 5% (1.050, 1.006–1.096) for heart failure with each 10 dB increment of road traffic noise; the risk of atrial fibrillation increased by 1.1% (1.011, 1.002–1.021) with each 10 dB increment of railway noise; and the risk increased by 1% (1.010, 1.003–1.017) for myocardial infarction, 2.7% (1.027, 1.004–1.050) for atrial fibrillation, and 2.3% (1.023, 1.016–1.030) for heart failure with each 10 dB increment in aircraft noise. Further, effects from road traffic, railway, and aircraft noise all followed positive linear trends with CVDs. Long-term exposure to traffic noise is positively related to the incidence risk of cardiovascular events, especially road traffic noise which significantly increases the risk of CVDs, stroke, and heart failure.